Analysis of Community Appreciation in Urban Governance Through 'Soul And Body' Approach in Bandung City - Albanah, Rosa saefi Yusuf; Harahap, Lailannur Fahradiza Hasiani; Irwan, Nadya Prasanti (Universitas Pendidikan Indonesia, 2023)
Urbanization encourages the development of urban structures that have an impact on urban development and governance systems. This study aims to determine the level of community appreciation and its influence on development through the 'soul and body' approach and the influence of the city's soul on the city's body to support the development of the city of Bandung. The results show that the indicators of the soul that have the highest value are identity, attachment, and satisfaction, while the indicators of the body that have the highest value include commercial services, culture and arts, and diversity, and there is a significant influence of the city's soul on the body of the city. It was concluded that the city of Bandung has a strong urban soul that has a positive effect on the city body. This indicates the appreciation of the community for improving the management and development of Bandung city. Recommendations for the government to seek in development to pay attention to community participation in planning and governance processes through collaborative planning techniques, strengthen communicative rationality and institutional planning through a sociological institutionalism approach to create urban prosperity and balance.